Optimization of Gelling Agent Peel-Off Face Masks Formula From Loaded Red Bracts of Kepok Banana Flower (Musa Paradisiaca L.) - Siti Fatimah Hanum; Satheesh Babu Natarajan; Muhammad Gousuddin; Rizka Angrainy (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
A peel-off facial mask is a cosmetic preparation in the form of a gel, which is applied to the skin of the face and left to dry so that a transparent film is formed that is elastic and easy to remove. One of the factors that influences the characteristics of peel-off gel face masks is the gel-forming ingredients which have different characteristic properties. The aim of this research was to determine the effectiveness of loaded red bracts of Kepok banana flowers (Musa paradisiaca L.) which were formulated into peel-off face maks with varying gelling agent concentrations. This research was carried out experimentally in the laboratory, including: taking plant samples using purposive sampling, sample processing and plant determination, making extracts using ultrasonic waves, making peel-off face mask preparations with gelling agent concentrations, physical evaluation of the preparations and stability test. The research results showed that the physical preparation of the peel-off face mask loaded with red bracts of Kepok banana flowers (Musa paradisiaca L.) was brownish red in color, odorless, gel texture, transparent, sticky, thick, non-synergic and homogeneous. The stability results show that there is a change in pH before and after test.